Analisis SWOT dalam Menentukan Strategi Pemasaran Produk UMKM Opak Kolontong - Ponirah, Ade; Yuliana, Resna; Nasution, Ade Iskandar (Journal of Islamic Economics and Business, 2021)
Management strategy as an art and science to formulate,Â implement, and evaluate organizational decisions to achiveÂ its goals. The marketing strategy that has been implementedÂ by the UMKM Opak Kolontong in Bojongkunci Village stillÂ uses a traditional system that is by supplying to the center forÂ souvenirs in Bandung. This product has the power that is notÂ fast stale without using preservatives. This product olso has aÂ disadvantage of not having a store and less attractiveÂ roughness. The opportunity for this product is to doÂ promotions using instagram and flavor. The threat of thisÂ product is the low sales level.